The Impact of Recognizing Impairment Losses Under PSAK 48 on Financial Performance and Investor Confidence - Thomas Alvando Winarto; Yusnaini Yusnaini (GLOBAL SCIENTS PUBLISHER, 2026)
The implementation of asset impairment testing under PSAK 48 (adopted from IAS 36) marks a fundamental shift in financial reporting, demanding continuous evaluation of the recoverable amount of long-lived assets and goodwill. However, the inherent flexibility and managerial subjectivity required in impairment testing create potential agency problems and complex market signaling. This study aims to develop a Systematic Literature Review (SLR) to comprehensively map the impact of asset impairment loss recognition on financial performance and investor confidence. Adopting the PRISMA guidelines, 35 primary articles ranging from 2013 to 2026 were analyzed using a thematic approach. The mapping results show a significant research focus on the duality of impairment impacts across various sectors, including manufacturing, banking, and state-owned enterprises. Research findings reveal that while the recognition of impairment losses inherently deteriorates short-term financial performance metrics (such as ROA and net profit), its effect on investor confidence is paradoxical. Through the lens of Agency Theory and Signaling Theory, it was found that transparent and timely impairment reporting serves as a positive signal of managerial integrity that sustains investor trust. Conversely, discretionary impairments driven by opportunistic motives, such as 'big bath' earnings management, significantly erode market confidence and exacerbate information asymmetry.